PENINGKATAN KAPASITAS KEPRIBADIAN DAN PUBLIC SPEAKING BAGI KELOMPOK SADAR WISATA, PELAKU USAHA, DAN PEMUDA PEGIAT WISATA DALAM MEMPERKENALKAN PRODUK PARIWISATA DI KABUPATEN BANGKA BELITUNG - Yang Gusti Feriyanti; Pepen Sumirat; Muhammad Sayaiputra; Muhammad Billi Putera Mas Agung; Bianda Arabella; Kinanti Tara Ramadhani; Seviana Anggreni (Nusantara Hasana Journal, 2025)
Public speaking is the skill of speaking in public to convey a message effectively, while personality development aims to improve internal and external aspects of oneself to be able to adapt and achieve one's best potential. Through community service activities carried out by the Bangka Regency Tourism Office, participants from tourism awareness groups, business actors, and young tourism activists were given training that included improving effective communication skills and personality development. The methods used included discussions, role-plays, and non-verbal communication exercises, which aimed to overcome obstacles such as nervousness and fear when speaking in public and increase participants' confidence in introducing regional tourism potential. The training results showed that participants were able to improve their competence, motivation, and confidence in promoting tourism products in Bangka Belitung and are expected to become a model for tourism human resource training in other regions. The community service activities organized by the Bangka Regency Tourism Office were successful and received a positive response from the participants. The material on effective communication, public speaking, and personality development presented at Gedung Juang, Bangka Regency, improved participants' competence and motivation in promoting the region's tourism potential. Through various methods such as discussions, role-plays, and non-verbal language exercises, participants became more confident and able to navigate complex communication situations in the tourism industry. It is hoped that similar activities can continue to be implemented sustainably to support the improvement of tourism human resources and local economic growth in Bangka Belitung.